Uji aktivitas antibakteri pasta gigi ekstrak biji duku (Lansium domesticum) terhadap Streptococcus mutans: Antibacterial Activity Test of Duku Seed (Lansium Domesticum) Extract Toothpaste Against Streptococcus Mutans - Azzahra Hanan Afni Caya; Shanty Chairani; Danica Anastasia (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2026)
Background: The main bacteria in dental caries is Streptococcus mutans. Toothpaste with herbal ingredients can be used to prevent dental caries. Duku (Lansium domesticum) seed extract has antibacterial activity against S. mutans because it contains many active compounds. The aim of this study was to determine the antibacterial activity of duku seed extract toothpaste against S. mutans. Methods: This study was an in vitro laboratory experimental study with a post-test only control group design and was divided into five groups, namely duku seed extract toothpaste 1.56%, 3.12%, 6.25%, commercial toothpaste (control positive), and placebo toothpaste (control negative). Antibacterial activity of the toothpastes against S. mutans tested using the disc diffusion method. The inhibition zone was measured with calipers in millimeters. Data were analyzed using the Kruskal wallis test and the Mann Whitney post hoc test. Results: The results of Kruskal wallis test showed that duku seed extract toothpaste in all concentration groups had a significant difference to the negative control (p<0.05), but there was no significant difference compared to the positive control (p>0.05). Conclusion: Duku seed extract toothpaste has antibacterial activity against S. mutans.